Cardiac resynchronization therapy delivered via a multipolar left ventricular lead is associated with reduced mortality and elimination of phrenic nerve stimulation: long-term follow-up from a multicenter registry - Behar, JM; Bostock, J; Zhu Li, AP; Chin, HMS; Jubb, S; Lent, E; Gamble, J; Foley, PWX; Betts, TR; Rinaldi, CA; Herring, N (Wiley, 2015)
Introduction Cardiac resynchronization therapy (CRT) using quadripolar left ventricular (LV) leads provides more pacing vectors compared to bipolar leads. This may avoid phrenic nerve stimulation (PNS) and allow optimal lead placement to maximize biventricular pacing. However, a long-term improvement in patient outcome has yet to be demonstrated.